A combined decision model for R&D project portfolio selection - (:unkn) unknown (Inderscience Publishers, 2008)
In this paper, a combined decision model for selecting and prioritising Research and Development (R&D) projects is proposed. The aim of this study is to provide a systematic approach for project portfolio selection. Analytic Hierarchy Process (AHP), Data Envelopment Analysis (DEA) and Value Tree Analysis (VTA) are implemented and combined in the proposed model to determine the efficient and feasible projects among the alternative R&D projects. The proposed model utilises both quantitative and qualitative information for project portfolio selection. The efficient projects with the higher feasibility scores have the higher priority over the alternative R&D projects. Decision-makers of R&D projects can use the proposed model to select the right projects, which are efficient and feasible using both quantitative and qualitative information available. Copyright © 2008, Inderscience Publishers.
Keywords: AHP; Analytic Hierarchy Process; Data Envelopment Analysis; DEA; Project portfolio selection; R&D projects; Value Tree Analysis; VTA